2008
DOI: 10.1590/s0102-09352008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in muscular enzymes of horses competing long-distance endurance rides under tropical climate

Abstract: Alterations in muscular enzymes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 11 publications
3
15
0
11
Order By: Relevance
“…It should be warned that CK-MB levels alone do not produce important information on the cardiac integrity of horses submitted to exercise. On the other hand, studies have suggested that the increase in the serum enzyme activity occurs due to the transitory increase in the permeability of the sarcolemma in the absence of histological lesions [28,29]. Positive correlations were observed for cTnI and CK-MB in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…It should be warned that CK-MB levels alone do not produce important information on the cardiac integrity of horses submitted to exercise. On the other hand, studies have suggested that the increase in the serum enzyme activity occurs due to the transitory increase in the permeability of the sarcolemma in the absence of histological lesions [28,29]. Positive correlations were observed for cTnI and CK-MB in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…Some of these changes have been studied in equestrian sports such as flat racing [2][3][4] , endurance [5][6][7] , show jumping [8,9] , eventing [10] , reining [11] , marcha [12] , cavalcade [13] , and polo [14,15] . However, to the best to our knowledge, there is no such a study focused on jereed horses.…”
Section: Introductionmentioning
confidence: 99%
“…Outros fatores, tais como desequilíbrio eletrolítico, deficiência de vit. E/selênio, infecção viral, distúrbios hormonais e regulação intracelular anormal de cálcio têm sido descritos como predisponentes (VALENTINE et al, 1998 excessiva, são identificados. Alguns equinos são incapazes de caminhar devido à dor e contratura muscular, particularmente nos músculos glúteo, bíceps femoral, semitendinoso, semimembranáceo e epaxial.…”
unclassified
“…A gravidade da condição nem sempre se relaciona à intensidade do exercício (HARRIS & MAYHEW, 2000). O diagnóstico da SRE é baseado nos sinais clínicos e na elevação da concentração sérica da creatina cinase (CK), do lactato desidrogenase (LDH) e da aspartato transaminase (AST) (TEIXEIRA-NETO et al, 2008).…”
unclassified